Why we should stop using animal-derived products on patients without their consent - Rodger, Daniel (Journal of medical ethics, 2022)
Medicines and medical devices containing animal-derived ingredients are frequently used on patients without their informed consent, despite a significant proportion of patients wanting to know if an animal-derived product is going to be used in their care. Here, I outline three arguments for why this practice is wrong. First, I argue that using animal-derived medical products on patients without their informed consent undermines respect for their autonomy. Second, it risks causing nontrivial psychological harm. Third, it is morally inconsistent to respect patients’ dietary preferences and then use animal-derived medicines or medical devices on them without their informed consent. I then address several anticipated objections and conclude that the continued failure to address this issue is an ethical blind spot that warrants applying the principles of respect for autonomy and informed consent consistently.